Perbandingan Biaya dan Waktu Pelaksanaan Konstruksi Bekisting Konvensional dan Sliding Form pada Pekerjaan Konduit di Bendungan Cijurey Paket 1 - Trianto, Adden; Tunggulgeni, Ekodjati; Suprayogi, Suprayogi (Universitas Ibn Khaldun, 2026)
In the Cijurey Dam Package I conduit construction project, formwork technology is an important aspect because it is entirely the responsibility of the contractor, so the implementation risks need to be minimized. Initially, the concrete casting method used conventional formwork that was made directly at the project site. However, developments in the construction world demand more efficient methods, leading to the emergence of alternatives such as the use of prefabricated formwork. One type used is sliding formwork. This study aims to evaluate the cost and time effectiveness between conventional formwork and sliding formwork, as well as analyze the reasons for their selection in the Cijurey Dam Package I conduit work. The research method was carried out by calculating the estimated cost and duration of conventional formwork, then comparing the results with the data on the use of sliding formwork in the project. The results show that the Cijurey Dam Package I Construction Project used sliding formwork at a cost of Rp 185.185,00 per square meter, with a cost difference of Rp 342.819.286,34 or about 12,37% cheaper than the calculation using conventional formwork, which averaged - average of Rp 211.332,06. In addition to cost and time considerations, sliding formwork has a faster construction time of 2 hours per tunnel block conduit compared to conventional formwork.